The influence of meteorological phenomena on the ecosystems of a tropical region, southeast coast of India: A case study - P Perumal (Ciencias Marinas, 1993)
The rainfall pattern at Parangipettai, southeast coast of India, for a period of a quarter century is given and the impact of rains on the hydrological and biological features is discussed. The total annual rainfall usually ranges between 1,200 and 1,400 mm. Generally, the bulk of annual precipitation occurs during the northeast monsoon. The climate of the area can be divided into four seasons in one year: monsoon, postmonsoon, summer and premonsoon. The heavy monsoonal downpour and the resulting heavy freshwater flow through the river exert influence on the characteristics of the waters of the coastal region and its ecosystems. Wind velocity data are also given and the role of wind in the transport of organic matter and nutrients, and in mixing processes is been discussed.